Co-producing Transition:Innovation Processes in Farms Adhering to Solidarity-based Purchase Groups (GAS) in Tuscany, Italy - Brunori, Gianluca; Rossi , Adanella; Malandrin, Vanessa (The International Journal of Sociology of Agriculture and Food, 2011)
The growth of localized and sustainable food systems is widely recognized in many Western countries as a response to the increasingly evident crisis of conventional food systems. However, despite the growing consumer demand, the producer capacity to catch up with demand emerges as a critical point. The authors reckon that participation in alternative food chains not only needs a new market opened, but also appropriate farming styles. Adopting new farming styles requires radical changes to knowledge and skills, material assets, organizational patterns, communication practices, etc. To that end, the direct interaction with consumers as well as the co-operation and co-ordination with other farmers become crucial. On the basis of a deep analysis carried out through a case-study – the innovation cycles activated by farmers adhering to Solidarity-based Purchase Groups (GAS) in Tuscany, Italy – the article explores the complex processes linked to transition, and tries to contribute to a theory of alternative food networks by representing changes in the farm as an outcome of interaction within hybrid networks through the definition of new codes, cognitive frames, norms, rules and organizational patterns.